Komodifikasi Nama Samaran Penyiar dalam Industri Radio : (Kajian terhadap Radio POP FM Semarang) - Suhariyanto; Saptiyono, Ami; Laksono, Agus Edy (IAIN Madura, 2025)
This research seek to understand how the radio industry operates in the era of media convergence, particularly in relation to media commodification. Here, the researcher will specifically describe the behavior of media workers in using pseudonyms in radio broadcasts. The research object is located at Radio Pop FM Semarang, Central Java. This research uses media economics theory with a political economy perspective. Additionally, the researcher will also analyze from the perspective of commodification, where one of the indicators is to obtain profit. This research will examine how media commodification practices at Radio POP FM are related to pseudonym sales strategies. This research uses a critical paradigm with a qualitative approach. The result of this research is that the use of pseudonyms or fake names in broadcasting media constitutes the commodification of names within the media itself.